Competitiveness of educational favour in the direction of the spesiality Sport Management in the educative market of Ukraine - Kudelko, V. E.; Kudelko, A. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: in this article the nature of the concept of sport management was studied, the main trends of the speciality Sport Management was analyzed, supply and demand of the education market was determined.